Study on Factors Affecting Performance in the Construction Business of Contractors in the Pakse Municipality, Champasack Province, Lao PDR Case study: Building construction business: https://doi.org/10.69692/SUJMRD0901100 - KHANTRY, Soukthavy; KHEOPANYA, Bounthavay; SANGVIBOUTH, Souvanh; KEOALOUNXAY, Sengaloun; DARAVONG, Sinthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this research is to examine the key factors that affect the construction business of the construction companies in the Pakse Municipality, Champasack Province of the Lao People's Democratic Republic, which include the business model and operations of the construction company, as well as the analyze of various factors that affect the success of the business. Additionally, the research investigates the causes and methods for preventing or resolving such issues, considering the project's two critical aspects. The data were obtained from 53 construction company utilizing questionnaires. The data was further statistically examined to determine the factors' relative relevance and test the hypothesis. Research results showed 12 major problems: 1) project owner does not pay the agreed-upon construction costs; 2) lack of pre-employment financial assessment; 3) lack of personnel planning; 4) lack of motivation to work; 5) inflation and country's economic insolvency; 6) registered capital and performance of the company; 7) overproduction and overpricing; 8) lack of mechanical planning; 9) lack of planning and control of material use; 10) competitors who are companies from other provinces or abroad; 11) shortage of subcontractors and skilled labor; 12) encouragement-promotion and knowledge of modern construction techniques from the government. Altogether, the two fundamental factors indicated that the most significant issue is within the project, specifically the finances and building budget, with an average mean score of 4.18, which is 100%. As for personnel and staff, the average mean score of 4.14 covers 100%. In terms of sourcing, the average mean score of 3.85, accounting for 83.33%; for tools and construction machinery, the average mean score of 3.78, representing 83.33%. Considering building materials, the average mean score of 3.74, forming 71.42%, and in terms of environment and regulations, the average mean score of 3.74, equivalent to 60 percent of the problems with an average mean score greater than 3.5. The hypothesis testing showed that the value is less than the value. In summary, factors that affect the operation of construction contractor businesses do not depend on whether the contractor is profitable or at a loss/equity, or the importance of the factors does not depend on performance.